Chemical constituents of dichloromethane extract from the stem bark of Garcinia fagraeoides - Thuy, Tran Thi Thu; Nguyet, Hoang Thi Minh; Thuy, Nguyen Phuong; Vu, Nguyen Nghia; Binh, Nugyen Quoc; Tai, Bui Huu`````; Giang, Phan Minh (Vietnam Journal of Science and Technology, 2022)
The Garcinia genus belonging to the Clusiaceae family (Guttiferae) has been reported to be a rich source of polyisoprenylated benzophenones, xanthones and biflavonoids with various biological activities. Garcinia fagraeoides A.Chev is an evergreen hardwood tree found only in the north provinces of Viet Nam and Guangxi province of China. Its stem bark and leaves have been used in Vietnamese traditional medicine for treatment of malaria and dermatitis diseases. In our continuing studies on chemical constituents and biological activities from the genus Garcinia, the phytochemical of Garcinia fagraeoides’s stem bark collected from Thua Thien Hue province was investigated. Repeated chromatography steps over silica gel and Sephadex LH-20 of the dichloromethane partition from the methanol extract of  Garcinia fagraeoides’s stem bark led to the isolation of five compounds including one polyisoprenylated benzophenone (isogarcinol (1)), two tetraoxygenated xanthones (rubraxanthone (2), a-mangostin (3)), ferulic acid (4), and pyromeconic acid (5). Their structures were elucidated mainly by analysis of their 1D, 2D NMR spectroscopy and ESI-MS data, and by comparison with reported data. The absolute configuration of isogarcinol (1) was determined by comparison of its experimental optical rotation and NMR data with the values of its stereoisomer. This is the first reported isolation of compounds 1-5 from the stem bark of Garcinia fagraeoides.